Solar Wind Particle Distribution Function Fitted via the Generalized Kappa Distribution Function: Cluster Observations - Qureshi,MNS; Pallocchia,G; Bruno,R; Cattaneo,MB; Formisano,V; Reme,H; Bosqued,JM; Dandouras,I; Sauvaud,JA; Kistler,LM; Möbius,E; Klecker,B; et al. (2003)
One of the major issues in space plasma physics is that in spite of the inhomogeneity of interplanetary plasma and the complicated magnetic field topology we do not find strong deviations from Maxwellian distributions as it would be expected for a quasi-collisionless plasma. However, the presence of high energy tail and shoulders in the profile of distribution function stimulate to look for a better analytic representation of the observed distributions. Therefore, here we adopt a non-Maxwellian distribution function such as the Ellipsian distribution function, which is the generalized form of the Kappa distribution function. In this paper we have analysed the solar wind data recorded by Cluster s/c during early 2001 and 2002 when the s/c were repeatedly immersed in the solar wind, ahead of the Earth's bow shock. Data were modeled with the help of the Ellipsian distribution function and values of the best fit parameters were successively used to characterize the solar wind kinetics at different locations of one of the four Cluster s/c.